REFLEKSI TAT TWAM ASI DALAM TANGGUNG JAWAB SOSIAL DI LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT NYUHKUNING - Ni Komang Urip Krisna Dewi; Putu Rany Wedasuari (Jurnal Ilmiah Global Education, 2023)
This research aims to contruct the Corporate Social Responsibility (CSR) based on Tat Twam Asi (TTA) in Lembaga Perkreditan Desa (LPD).  This study aims to analyze social responsibility or Corporate Social Responsibility (CSR) based on Tat Twam Asi (TTA) in Village Credit Institutions (LPD). The research was conducted at LPD Nyuhkuning. The research was carried out using a qualitative approach with in-depth interviews with several informants, observations and documentation. This research shows that the value of Tat Twam Asi that is actualized in the CSR carried out at LPD Nyuhkuning is the wealth of the LPD that is allocated to the villagers and the surrounding environment. Tat Twam Asi which means I am you and vice versa. The value of Tat Twam Asi in social responsibility is actualized by the LPD management by taking responsibility as administrator and carrying out the allocation of funds for ceremonial activities in the village and social activities, as well as concern for the environment.